Innovative Educational Management Model of the School Principals to improve Discipline and Personality of Elementary School Students in the Digital Era - Rohmanuddin Ahmad; Mohammad Syaifuddin; Arif Wurianto (LP. Ma'arif Janggan Magetan, 2026)
The rapid advancement of digital technology has transformed educational practices while simultaneously posing challenges to the development of discipline and character among elementary school students. This study aims to develop and evaluate an innovative digital-based educational management model to strengthen students’ discipline and character. Using a Research and Development (R&D) approach with the ADDIE framework, the study involved the stages of analysis, design, development, implementation, and evaluation. The resulting model integrates three key components: a QR Code–based digital attendance system, a discipline point system applying reward and punishment principles, and a digital teacher journal for monitoring daily student behavior. Expert validation indicated a very high feasibility level (93.33%). Statistical analysis using a paired samples t-test revealed significant improvements in students’ discipline scores (from 42.95 to 52.50) and character scores (from 42.25 to 51.35), with p = 0.000 (< 0.05). Qualitative findings further supported these results, showing increased responsibility, politeness, rule compliance, and enhanced collaboration between teachers and parents. The findings suggest that digital-based educational management is an effective strategy for strengthening student character holistically through adaptive, collaborative, and visionary school leadership in the digital era.